O Aspergillus sp. NA AVALIAÃ‡ÃƒO DA DEFICIÃŠNCIA DO POTÃSSIO NO SOLO - Pereira, A. Lima G.; Abreu, Oldemar C.; Zagatto, A. G. (REVISTA DE AGRICULTURA, 2016)
O Aspergillus sp. NA AVALIAÃ‡ÃƒO DA DEFICIÃŠNCIA DO POTÃSSIO NO SOLO